Targeted quantification of the glycated peptides of human serum albumin - Garikapati, Vannuruswamy; Korwar, Arvind M.; Jagadeeshaprasad, Mashanipalya G.; Kulkarni, Mahesh J. (Methods in Molecular Biology, 2017)
Glycated human serum albumin (HSA) serves as an important marker for monitoring the glycemic status. Developing methods for unambiguous identification and quantification of glycated peptides of HSA using high-throughput technologies such as mass spectrometry has a great clinical significance. The following protocol describes the construction of reference spectral libraries for Amadori-modified lysine (AML), N(ε)-(carboxymethyl) lysine (CML)-, and N(ε)-(carboxyethyl)lysine (CEL)-modified peptides of synthetically modified HSA using high-resolution mass spectrometers. The protocol also describes work flows, for unambiguous identification and quantification of glycated modified peptides of HSA in clinical plasma using standard spectral libraries by various mass spectrometry approaches such as parallel reaction monitoring (PRM), sequential window acquisition of all theoretical fragment ion spectra (SWATH), and MSE.